Разработка новых схем резистивной защиты высоковольтных конденсаторов мощных емкостных накопителей энергии от аварийных токов - Баранов, М.И.; Рудаков, С.В. (Електротехніка і електромеханіка, 2015)
Приведены результаты разработки новых схем резистивной защиты высоковольтных импульсных конденсаторов
мощных емкостных накопителей энергии от разрушающего действия на них аварийных импульсных токов амплитудой
до сотен килоампер, протекающих при отсутствии подобной защиты через данные конденсаторы при электрическом
пробое их внутренней или наружной изоляции. Приведені результати розробки нових схем резистивного захисту високовольтних імпульсних конденсаторів потужних
ємкісних накопичувачів енергії від руйнівної дії на них аварійних імпульсних струмів амплітудою до сотень кілоампер,
що протікають за відсутності подібного захисту через дані конденсатори при електричному пробої їх внутрішньої
або зовнішньої ізоляції. Purpose. Development of new charts of capacitance-resistance
defense of high-voltage capacitors of powerful capacity stores of
energy (CSE) from emergency large impulsive currents (LIC) at
the electric hasp of one of condensers of such CSE on the stage
of their charge or discharge. Methodology. Electrophysics
bases of the technique of high-voltage and large pulsed currents, and also scientific and technical bases of planning of
devices of high-voltage impulse technique. Results. Two new
charts of capacitance-resistance defense of high-voltage impulsive capacitors are offered for powerful CSE of one- and multimodule execution from emergency LIC, being based on the use
of high-voltage permanent graphite-ceramic resistors of type of
TVO-60 a face value from 24 to 100 Ohm, set on the highvoltage conclusions of all of condensers of CSE. One of the developed capacitance-resistance charts of defense of condensers
for powerful one-module CSE passed practical approbation.
Originality. It is shown that application of the developed charts
of capacitance-resistance defense of high-voltage condensers of
powerful CSE is provided by frequent limitation of amplitude of
emergency LIC, flowing through broken through an electric
discharge condenser of CSE on the stage of his charge or discharge. Such limitation emergency LIC is prevented by explosion destruction of the damaged condenser of high-voltage CSE.
Practical value. The use of the developed charts of capacitanceresistance defense of high-voltage capacitors from emergency
LIC allows substantially to promote functional safety of powerful CSE of one- and multi-module execution and provide the safe
terms of labour for a scientific and technical personnel, attendant similar CSE.